Exploring Adolescent Faith Articulation among At-Risk Urban Youth - Severe, Mike (Christian education journal, 2020)
Adolescents have significant capacity to engage in theological inquiry and theological reflection. How do at-risk teens articulate their faith and practice? This study explores how at-risk youth practice and articulate their beliefs through semi-formal qualitative interviews. This research suggests a caution to a simple therapeutic interpretation of adolescents’ faith without first taking into account the traumatogenic nature of their environment. Best practices for faith articulation and recommendations for further study are included.